THE MANAGEMENT OF TEACHER PERFORMANCE AT MADRASAH IBTIDAIYAH TERPADU AL IHSAN IN SELAT LANCANG, TANJUNGBALAI - Putri Nian (UIN Sumatera Utara Medan, 2022)
This study aims to see teacher performance in planning and organizing at Madrasah Ibtidaiyah Terpadu Al Ihsan in Selat Lancang, Tanjungbalai. Supervision of teacher performance was carried out by the head of the Madrasah Ibtidaiyah Terpadu Al Ihsan in Selat Lancang, Tanjungbalai. The study also focuses on supporting and inhibiting factors for teacher performance management at the Madrasah Ibtidaiyah Terpadu Al Ihsan in Selat Lancang, Tanjungbalai. This research follows a qualitative approach, namely a naturalistic approach. The term naturalistic indicates that the implementation of this research does occur naturally, in good normal situations, and is not manipulated by circumstances and conditions. Teacher performance planning at the Madrasah Ibtidaiyah Terpadu Al Ihsan in Selat Lancang, Tanjungbalai is considered quite good because effective teachers have quality abilities and attitudes who can provide the best for students, such as fun teaching and learning process.